The Effectiveness of Teaching English Vocabulary in the theme of "Animals And Plants" Using Crossword Puzzle - Heru Setiawan (Jurnal Didascein Bahasa, 2015)
ABSTRACT: The objective of this study was to find out whether or not it was effective teaching English vocabulary in the theme of "Animals and Plants"Â using crossword puzzle. The population of this study was the seventh grade students of Junior High School Sriwijaya of Palembang in the academic year 2013/2014. The sample was taken from one class that consists of 30 students through convenience non-random sampling. The method of this study was the pre-experimental method with one group pre-test and post-test design. The data were obtained by means of the test, the result were analyzed through matched t-test formula. Based on the study, it was to found that teaching English vocabulary in the theme of "animals and plants" using crossword puzzle to the seventh grade students of Junior High School Sriwijaya of Palembang was effective. The students' score has increased from 67.7 in the pre-test to 85.08 in the post-test and it was found that t-test was higher than t-table (7.3 > 1.697). It means that teaching English vocabulary in the theme of "animals and plants"Â using crossword puzzle was significantly effective.Â Key words: vocabulary, animals and plants theme, crossword puzzleÂ Â